2006
DOI: 10.1007/s10704-006-0048-9
|View full text |Cite
|
Sign up to set email alerts
|

Energy considerations in crack deflection phenomenon in single crystal silicon

Abstract: Crack deflection in single-crystal brittle occurs when a crack, propagating on one cleavage plane, 'chooses', from energy considerations, to continue propagating on another cleavage plane. This phenomenon was identified during dynamic crack propagation experiments of thin, rectangular [0 0 1] single-crystal (SC) silicon specimens subjected to three-point bending (3PB). Specimens with long pre-cracks (hence propagating at a 'low' energy and velocity) cleave along the vertical (1 1 0) plane, while the same speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Because cleavage cracking in silicon can take place on both {111} and {110} planes and the surface free energies of them are only slightly different, [7,8] within the same crystal, the crack surface may shift among cleavage facets that are of similar orientations, resulting in relatively wavy flanks. Once the crack front reaches a grain boundary, if the orientations of the two grains are considerably different, especially when the twist misorientation angle is relatively large, the crack must overcome a significant barrier effect to enter into the next grain.…”
Section: Introductionmentioning
confidence: 99%
“…Because cleavage cracking in silicon can take place on both {111} and {110} planes and the surface free energies of them are only slightly different, [7,8] within the same crystal, the crack surface may shift among cleavage facets that are of similar orientations, resulting in relatively wavy flanks. Once the crack front reaches a grain boundary, if the orientations of the two grains are considerably different, especially when the twist misorientation angle is relatively large, the crack must overcome a significant barrier effect to enter into the next grain.…”
Section: Introductionmentioning
confidence: 99%
“…, many orders of magnitude below that described by Sherman (2006). However, the images show that the crack moves in a series of jumps in which the crack moves at a speed greater than the 6 m s À1 resolution limit, followed by a stop time of between 1 and 2 ms.…”
mentioning
confidence: 77%
“…The result is that the larger surface area of the {111} planes increases the cleavage energy by a factor of 1.225, making fracture on the {110} planes favourable, as is observed during the fabrication of semiconductor device die and microelectromechanical sensor (MEMS) devices. This {110} cleavage occurs for low crack velocities (below about 1500 m s À1 ), but when the crack velocity becomes high, (above about 3000 m s À1 ), propagation entirely on the {111} planes is observed (Sherman, 2006). At intermediate velocities, propagation starts on the {110} planes but then switches to {111}, driven, it is suggested, by the energetics of phonon emission.…”
Section: à2mentioning
confidence: 93%
“…[7,8]. Furthermore, many theoretical studies have also shown that when Si is subjected to mechanical stresses at ambient temperature, it will cleave in the planes with the low bond densities into {111} as the most preferred cleavage plane before propagating in the <110> or <112> directions [9][10][11]. Therefore, the different fracture planes will have different bond densities, resulting in different fracture strength.…”
Section: Finite Element Methodsmentioning
confidence: 99%